A combined capacitor current balancing method with weighting factor control for multi‐string LED drivers - Hajar Sedghi; Mohammad Sarvi (IET Circuits, Devices and Systems)
Abstract A multi‐string LED lamp driver is presented involving a boost converter and a multi‐output CLL resonant converter as the first and second stages, respectively. The CLL resonant converter works in a fixed resonant frequency, and output currents are controlled by the boost converter regulated by the Weighting Factor control method. Also, the boost converter improves and controls its input voltage. Since CLL resonant converters operate at fixed resonant frequency, primary‐side MOSFETs can achieve zero voltage switching, while secondary‐side rectifier diodes achieve zero current switching. A prototype of the proposed system was constructed to verify the theoretical results by practical implementation. Also, the general features of the proposed structure were compared with some other similar works. Results confirmed the accuracy and favourable performance of the proposed system. In fact, the proposed LED driver achieved good current balancing in a wide range of input voltage and unbalanced loads making the structure potentially suitable for application in solar home systems (SHS).